SJS/TEN 2019: From science to translation. Issue 1 (April 2020) - Chang, Wan-Chun; Abe, Riichiro; Anderson, Paul; Anderson, Wanpen; Ardern-Jones, Michael R.; Beachkofsky, Thomas M.; Bellón, Teresa; Biala, Agnieszka K.; Bouchard, Charles; Cavalleri, Gianpiero L.; Chapman, Nicole; Chodosh, James; et al.
Abstract: Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) are potentially life-threatening, immune-mediated adverse reactions characterized by widespread erythema, epidermal necrosis, and detachment of skin and mucosa. Efforts to grow and develop functional international collaborations and a multidisciplinary interactive network focusing on SJS/TEN as an uncommon but high burden disease will be necessary to improve efforts in prevention, early diagnosis and improved acute and long-term management. SJS/TEN 2019: From Science to Translation was a 1.5-day scientific program held April 26–27, 2019, in Vancouver, Canada. The meeting successfully engaged clinicians, researchers, and patients and conducted many productive discussions on research and patient care needs.